2020
DOI: 10.3390/app10249054
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on the Evolution Mechanism of the Crater under a Millisecond Laser

Abstract: A two-dimensional numerical model considering recoil pressure and Hertz-Knudsen ablation rate was established on the foundation of the laser remelting model to investigate the influence of laser processing parameters on crater feature and melted zone, and it was verified through experiments. The temperature and flow velocity distribution of the molten pool during the formation of the crater were analyzed. The results showed that the ablation velocity could be considered under a higher laser peak power density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…established a 2D numerical model to analyze the influence of laser processing parameters on a crater feature and a melted zone and verified it through experiments. [ 52 ] The results showed that laser peak power density and pulse duration greatly affected the depth and diameter of the crater. With increasing pulse duration after 1.5 ms, the height of the edge bulge decreased.…”
Section: Laser Micro/nanostructuring Strategiesmentioning
confidence: 99%
“…established a 2D numerical model to analyze the influence of laser processing parameters on a crater feature and a melted zone and verified it through experiments. [ 52 ] The results showed that laser peak power density and pulse duration greatly affected the depth and diameter of the crater. With increasing pulse duration after 1.5 ms, the height of the edge bulge decreased.…”
Section: Laser Micro/nanostructuring Strategiesmentioning
confidence: 99%
“…The heat flux on metal surface mainly includes laser heat source, evaporation heat flux, boundary convection loss and so on [24,28]. The heat flux as the heat source needs to be added to the energy conservation equation.…”
Section: Boundary Conditionsmentioning
confidence: 99%